The role of crop diversity in climate change adaptation: insights from local observations to inform decision making in agriculture - Labeyrie, Vanesse; Renard, Delphine; Aumeeruddy-Thomas, Yildiz; Benyei, Petra; Caillon, Sophie; Calvet-Mir, L.; M Carrière, Stéphanie; Demongeot, Marilou; Descamps, Elsa; Braga Junqueira, André; Li, Xiaoyue; Locqueville, Jonathan; et al. (Current Opinion in Environmental Sustainability, 2021)
Homogenization of crop portfolios from the field to the global scale is raising concerns about agricultural adaptation to climate change. Assessing whether such trends threaten farmers’ long-term adaptive capacity requires a thorough understanding of changes in their crop portfolios, identification of the drivers of change, and the implications such changes have for local nutrition and food production. We reviewed the available literature on farmers’ reports of climate-driven crop changes. Small-scale farmers tend to adopt water-demanding crops, even in areas where models predict that reduced rainfall will reduce yields. The adoption of horticultural cash-crops combined with the abandonment of subsistence cereals modifies farmers’ nutritional inputs in terms of calories and nutrients, potentially undermining their food security. Farmers’ knowledge contributes to understand trends in crop diversity and support the design of strategies for adaptation to climate change. © 2021 Elsevier B.V.